PHASE EQUILIBRIA CONSTRAINTS ON RELATIONS OF ORE-BEARING INTRUSIONS WITH FLOOD BASALTS IN THE NORIL'SK REGION, RUSSIA - Latypov R.M. (My University, 2002)
Phase equilibria analysis has been performed to elucidate whether ore-bearing Noril'sk-and poorly mineralized Lower Talnakh-type intrusions are co-mag-matic with the extremely Ni-, Cu-and PGEs-depleted and not depleted flood basalts, respectively. The parental magma of the intrusions is classified as silica-undersat-urated olivine basalt, whereas that of the flood basalts is assigned to silica-saturated tholeiite. The plutonic equivalent of the former parental magma is olivine gab-bro or melagabbro, whereas the latter is gabbronorite. Phase equilibria relations clearly show that these two types of magmas cannot be co-magmatic as there is no way to derive one liquid from another by fractional crystallization. This provides no support for the current model considering the Noril'sk-type intrusions as exit conduits for a great volume of volcanic magma, which lost most of its chalcophile elements in the shallow settling chambers on its way to surface. The association of a large volume of chalcophile element-depleted basalts with the very sulfide-rich intrusions in the Noril'sk region is most likely coincidental and cannot, therefore, be used as a regional criterion when prospecting for the Noril'sk-type sulfides deposits in other flood basalts provinces.